Diagnostic potential of plasma CD30(+) small extracellular vesicles in Hodgkin lymphoma - K. E. Katsuba; L. A. Kramynin; M. A. Slyusarenko; A. V. Shalaev; V. V. Sharoyko; A. A. Valitova; A. S. Artem’eva; P. I. Krzhivitskiy; L. V. Filatova; A. V. Malek (Онкогематология, 2023)
Background. In current clinical practice, there are no reliable methods to stratify patients with a high risk of relapse or with a primary refractory form of Hodgkin lymphoma. Quantification of CD30-positive small extracellular vesicles (CD30(+)SEV) in plasma seems to be a possible approach to solve this issue. CD30(+)SEV can be quantified by the AuNP aptasensor technology based on the enzyme-mimetic properties of gold nanoparticles and the CD30-specific affinity of DNA aptamers.Aim. To quantify CD30(+)SEV in the plasma of patients with newly diagnosed Hodgkin lymphoma; to investigate the links between estimated parameter and clinical/morphological properties of disease and the effect of first two chemotherapy cycles.Material and methods. A semi-quantitative analysis of CD30(+)SEV in the plasma of patients with Hodgkin lymphoma (n = 55) was performed using the AuNP aptasensor. The relationship between the CD30(+)SEV concentration and the data of standard diagnostic approaches was evaluated through the r-Pearson correlation coefficient, the Mann–Whitney and Kruskal–Wallis criteria.Results. The plasma concentration of CD30(+)SEV in patients with Hodgkin lymphoma correlates with the quantity of CD30(+) cells in tissues of biopsied lymph nodes (r = 0.8) and the total lesion glycolysis estimated by PET/CT (r = 0.9). Patients with a relatively high concentration of CD30(+)SEV are characterized by an increase of erythrocyte sedimentation rate and leukocytosis compared with patients with a lower concentration of CD30(+)SEV. Two cycles of chemotherapy reduced CD30(+)SEV concentration, and this effect was more pronounced in patients treated with ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) regime than the BEACOPPesc (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, prednisolone, procarbazine).Conclusion. AuNP-aptasensor can be used for semi-quantitative assessment of CD30(+)SEV in plasma. The estimated CD30(+)SEV concentration correlates with the clinical and morphological parameters of patients with Hodgkin lymphoma and may reflect the severity of the disease. To assess the diagnostic and/or prognostic potential of developed technology, large-scale multicenter studies are required.